Zabójstwa w ujęciu projektu kodeksu karnego z 1993 roku - Tarnawski, Maciej (Wydział Prawa i Administracji UAM, 1994)
The author describes the provisions of law on homicide contained in the draft Penal Code of 1993. Several novelties are noticed in comparison with the Code currently in force. The chapter on crimes against life and body is placed differently. Provisions on homicide, especially infanticide and murder, are drafted specifically and not synthetically. The penal law protection of an unborn child including a child capable of independent survival is given a new shape. The proposed solutions are presented against the background of the law in force and their soundness is discussed. Problems arising in this connection and concerning legal qualification of acts as various types of homicide are also considered.
Homicide under the draft Penal Code of 1993